Phytochemical analysis, FTIR fingerprint and bioactivity of crude extract and fractions of Mesua ferrea L. - Dwi Hartanti; Zainur Rahman Hakim; Anna Nurlativah; Arinda Nur Cahyani; Fadhilah Zahra Nadia; Asmiyenti Djaliasrin Djalil (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Mesua ferrea L. (Ceylon ironwood, Calophyllaceae) is a popular medicinal plant with a long history in South and Southeast Asia folk medicines. In this study, we report the phytochemical analysis, FTIR fingerprint, as well as antimicrobial and antioxidant activities of the crude extract of leaves of M. ferrea and its fractions. The dried leaves of M. ferrea were extracted with ethanol by the re-maceration method. The crude extract was further partitioned in ethanol-water and ethyl acetate to obtain ethanol and ethyl acetate fractions, respectively. The identification of compounds in the extract and fractions was conducted according to the standard phytochemical screening method. Fourier-transform infrared spectroscopy (FTIR) was utilized to record their metabolites fingerprint. The antimicrobial activity was evaluated with the disk diffusion method against Escherichia coli, Bacillus subtilis, Candida albicans, and Saccharomyces cerevisiae. The antioxidant activity assay was conducted with 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging method. The crude extract of M. ferrea leaves and it fractions contained saponins, phenolic compounds, flavonoids, and terpenoids. The FTIR data supported the presence of terpenoids and glycosides in those samples as well. The extract and fractions demonstrated considerable antimicrobial activity against all tested bacteria and fungi, with MIC values ranged 3.9-31.3 μg/ml. The ethyl acetate fraction of M. ferrea leaves showed a moderate antioxidant activity with an IC50 value of 49.19 μg/ml.